CHANGES IN PERIODONTAL MICROCIRCULATION IN PATIENTS WITH ARTIFICIAL CROWNS - Pardayev D. S.; Rashidov R. A.; Said Kamil K.; Dadabayeva M. U. (Galaxy International Interdisciplinary Research Journal, 2022)
It is the circulatory system that first adapts to the new conditions of functioning of the homeostatic system, which is manifested by the development of vascular reactions at the level of the microvasculature. Among the early signs of the presence of pathological processes are metabolic changes resulting from disturbances in the supply of tissue as a system of arterioles, venules, capillaries, arteriolo-venular anastomoses, and lymphatic structures. One of the most frequent complications that directly affect the result of prosthetics is gum recession. According to different authors, its prevalence ranges from 45.5% to 85.1% in the adult population[3;4]. Researchers agree that the frequency of gum recession increases with age, which requires a special approach when planning orthopedic treatment. A similar situation is observed in patients already on orthopedic treatment with non-removable orthopedic structures. The frequency of periodontal complications in prosthetics with artificial crowns, the initial manifestation of which is gum recession, reaches more than 50%[6]. In this regard, the purpose of our study was to study the indicators of microcirculation in patients with gum recession as an independent form of periodontal disease and in patients wearing artificial crowns.